ISLAMISASI PSIKOLOGI - Rahayu, Iin Tri (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2004)
Islamization of psychology, in fact, is the effort to meet between Islamic doctrines and theories of psychology, or an effort how to explain psychological problem in the way of Islamic perspective. To achieve this purpose, there are two methods: pragmatism and idealism.Pragmatism method is an effort to appear Islamic psychology by giving priority on practice realization; adopted theories of western psychology, which has been establish, then searching for legitimating from the sacred text both al-Qur’an and hadits. In other side, idealism method is an effort to develop Islamic psychology based on the teaching and resources of Islamic knowledge itself. Furthermore, the theories of Islamic psychology that have been resulted is compared to the western psychology theories.Keywords: Psychology, Western, and Islam.